2014
DOI: 10.1017/jfm.2013.678
|View full text |Cite
|
Sign up to set email alerts
|

Flow topology in the wake of a cyclist and its effect on aerodynamic drag

Abstract: Three-dimensional flows around a full-scale cyclist mannequin were investigated experimentally to explain the large variations in aerodynamic drag that are measured as the legs are positioned around the 360 • crank cycle. It is found that the dominant mechanism affecting drag is not the small variation in frontal surface area over the pedal stroke but rather due to large changes in the flow structure over the crank cycle. This is clearly shown by a series of detailed velocity field wake surveys and skin fricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
59
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 13 publications
11
59
1
Order By: Relevance
“…Furthermore, relating changes in the leg orientation of a cyclist to the wake flow topology recently provided new insights for cycling aerodynamics (e.g. Crouch et al 2014).…”
Section: 83 Page 2 Of 14mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, relating changes in the leg orientation of a cyclist to the wake flow topology recently provided new insights for cycling aerodynamics (e.g. Crouch et al 2014).…”
Section: 83 Page 2 Of 14mentioning
confidence: 99%
“…Despite the simple geometry, the flow exhibits an unsteady, turbulent wake with complex vortex interactions (e.g. Achenbach 1972;Brücker 2001) mimicking conditions also encountered behind ground vehicles (Ahmed et al 1984) or cyclists (Crouch et al 2014). The experiments determine the time-average drag and a detailed comparison is made with data available from literature.…”
Section: 83 Page 2 Of 14mentioning
confidence: 99%
“…The oscillating frequency of 2.5 Hz is the lowest possible limit in this experimental set-up. In order to make the frequency of pedaling less than 2 Hz (The practical pedaling frequency is less than 2 Hz [2]), the present motor should be replaced for the more powerful motor in the future.…”
Section: Two Oscillating Cylinders In the Tandem Arrangementmentioning
confidence: 99%
“…It was reported that the dominant mechanism affecting drag is due to large changes in the flow structure on the basis of three-dimensional flows around a full-scale cyclist mannequin [2]. Two characteristic flow regimes are identified, corresponding to symmetrical low-drag and asymmetrical high-drag regimes, in which the primary feature of the wake is shown to be a large trailing streamwise vortex pair, orientated asymmetrically in the center plane of the mannequin.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclists are painfully aware that legs are not very aerodynamic resulting in, one assumes, a tremendous amount of drag. Thanks to the recent article by Crouch et al (2014) we may finally have an answer to this conundrum.…”
Section: Introduction: On Drag and Cyclingmentioning
confidence: 99%